1984
DOI: 10.1246/bcsj.57.3074
|View full text |Cite
|
Sign up to set email alerts
|

Acid Dissociation Constants of Alkyl Xanthic Acids and Formation Constants of Cadmium(II) and Zinc(II) Xanthato Complexes in 1:1 v/v H2O-DMF Medium

Abstract: The overall formation constants, β3, of cadmium(II) and zinc(II) complexes with alkyl xanthates (O-alkyl dithiocarbonates) were determined by polarography in the 1:1 v/v water–N,N-dimethylformamide mixture. The values of these constants increase in the order, methyl<ethyl<propyl<butyl<2-methylpropyl<1-methylethyl xanthate. This order agrees entirely with the order of the basicity of alkyl xanthates determined by using the kinetic parameter of the acid decomposition of xanthat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Cadmium sorption can be inhibited only by anions forming sufficiently stable complexes. Stability constants (log k) of cadmium with Cl − , SO 4 2− , CO 3 2− , CN − and xanthate are 1.98, 2.4, 4.02, 18.78 and 14.55, respectively [18,[23][24][25]. As expected from the low stability constant values of chloride, sulfate and carbonate they did not have much effect on the adsorption behavior of cadmium (Table 5).…”
Section: Effect Of Cations and Anionsmentioning
confidence: 77%
“…Cadmium sorption can be inhibited only by anions forming sufficiently stable complexes. Stability constants (log k) of cadmium with Cl − , SO 4 2− , CO 3 2− , CN − and xanthate are 1.98, 2.4, 4.02, 18.78 and 14.55, respectively [18,[23][24][25]. As expected from the low stability constant values of chloride, sulfate and carbonate they did not have much effect on the adsorption behavior of cadmium (Table 5).…”
Section: Effect Of Cations and Anionsmentioning
confidence: 77%
“…For the protonation of XANT, we could only find a single value, pK a = 2.20, obtained in a 1:1 mixture of water and dimethylformamide (8); in the absence of any other data, this value was used. To estimate the log β 2 value for the Cd(XANT) 2 0 complex, we again used the Irving-Rossotti approach with the Cd-Pb pairing.…”
Section: Ethylxanthatementioning
confidence: 99%
“…For DDC, speciation simulations were run with log K a values up to 7 (i.e., a factor of ~3800 times higher than the value in the NIST database, 3.42); the effect on Cd speciation at pH 5.5 was negligible (i.e., the dominant form remained Cd(DDC) 2 0 , as at pH 7.0). For XANT, we ran speciation simulations with log K a values up to 5.8 (i.e., a factor of ~4000 times higher than the value in Hayashi et al (8)) and again in this case the effect on Cd speciation at pH 5.5 was negligible (i.e., the dominant form remained Cd(XANT) 2 0 , as at pH 7.0). It can be concluded that the CdL 2 0 complexes are sufficiently strong to resist dissociation at pH 5.5.…”
Section: S10mentioning
confidence: 99%
“…Dialkyldithiocarbamate [SC(S)NRJ and alkylxanthate [SC(S)OR] are susceptible to an inactivating acid catalyzed hydrolysis. Whereas the acid decomposition rates for these two classes are approximately equal at pH 3, alkylxanthates are decomposed approximately 100-times more slowly at pH 5 (Hayashi et al, 1986 andHayashi et al, 1984). In the presence of a limited excess of chelating reagent, theu relative stability in acidic media can become an important factor for the success of the extraction.…”
Section: Resultsmentioning
confidence: 99%